Establishing a multicultural learning environment based on active knowledge exchange and mutual trust between teachers and students - Artëm Ingmar Benediktsson (Nordic Journal of Comparative and International Education, 2021)
Cultural and linguistic composition of the population of Iceland is constantly expanding. This brings new opportunities as well as challenges to the educational institutions that need to adapt to the new reality. Culturally responsive teaching and assessment methods have become increasingly important to motivate all students and provide them with equal opportunities. The research project, “It is not only the Teacher who is Talking; It is an Exchange”, was the first extensive qualitative study conducted in Icelandic universities to investigate immigrant students’ experiences of the learning environments and teaching methods. Forty-one first-generation immigrants participated in the study. The findings provided a deep insight into immigrant students’ experiences of being university students. The study brought to the forefront challenges that the participants experienced during the educational process, including language related issues, shortage of appropriate educational support and lack of clear policies regarding special assistance during examination periods. Furthermore, the study highlighted the importance of establishing a multicultural learning environment where every student has equal access and opportunity for personal development.